Pengaruh Potensi Sumber Daya Alam Dan Indeks Pertumbuhan Manusia (IPM) Terhadap Pertumbuhan Ekonomi Di Desa Hantakan Kabupaten Hulu Sungai Tengah - Agustina, Eka Santi; Latte, Jumai (Universitas Lambung Mangkurat, 2023)
Hantaka Village in the Hulu Sungai Tengah Regency of the South Kalimantan Province served as the background for this study's data collection in support of the study's objectives. In the philosophy of positivism, sampling is typically done at random, research instruments are used for data collection, and quantitative and statistical methods are used for data analysis. There are 1,501 people in the population, and 45 of them make up the sample. Hair et al.'s (2014) theory: 173. As a result, the following findings are obtained: 1. The results of the t test indicate that the variable potential of natural resources (X1) has a magnitude influence of 62.1 percent and a significant level of 0.000, or less than 0.05, indicating that Ho is rejected and Ha is accepted, indicating that the potential of natural resources (X1) has an effect on economic growth in Hanntak Village, Hulu Sungai Tengah Regency. 2. The results of the t test indicate that the variable human growth index (IPM) (X2) has a magnitude influence of 20% and a significant level of 0.094, or less than 0.05, indicating that Ho is accepted and Ha is rejected. This indicates that the human growth index (IPM) (X2) has an effect on economic growth in Hanntak Village, Hulu Sungai Tengah Regency, but not significantly. 3. The potential impact of natural resources and the human growth index (IPM) on economic growth in Hanntak Village, Hulu Sungai Tengah Regency, accounted for 51.10 percent of the independent variables. The remaining 48.90 percent was influenced by other factors that were not examined in this study Keywords: Economy, Growth Index, Natural Resources